The investment of time and professional skill at risk in the Built Environment in South Africa: an exploratory study - Ndlovu, Pride (My University, 2015)
For a long period of time, most built private sector clients in South Africa have been procuring the services of built professional consultants at risk. The concept of working at risk is also referred to as speculative work. It is not known and clear when the practice started or how it originated in South Africa but the practice takes place and appears to becoming increasing prevalent. This study is an exploratory study that investigates the concept of working at risk in detail and establishes the relationship between non-remuneration, motivation and performance when working at risk. The study was motivated by the fact that limited academic research has been done locally on the early phase of project delivery, which is considered a key stage of a project. Attention is generally drawn to the implementation phase and conclusions are drawn from this stage which could possibly impact on the early phase of the project. This study examines the general understanding of the concept by respondents and determines the relationship between payment, time and performance. Largely the academic research conducted on the implementation stage shows that the non-remuneration or non-payment of contractors affects their performance and existence. Similarities in general can be drawn from this. However, this study does not explore this approach as initial academic data on the subject is not readily available. The study is an exploratory study that collects qualitative data from experienced professionals that undertake risk work for their clients. Interviews conducted with the professionals produced valuable qualitative data on the concept and key findings were drawn from this input. The greater understanding of the practice can lead to a better understanding between parties, regulation of the practise, support for smaller firms and assist in building the economy of South Africa. The findings reveal that there is a common understanding of the concept and the non-payment of professionals over long periods whilst undertaking risk work does affect motivation levels and impedes performance, thereby supporting the findings of the literature.
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Building.
Keywords: Construction industry; Unemployment; South Africa; Employees|